2007
DOI: 10.1038/nm1488
|View full text |Cite
|
Sign up to set email alerts
|

Self-antigen tetramers discriminate between myelin autoantibodies to native or denatured protein

Abstract: The role of autoantibodies in the pathogenesis of multiple sclerosis (MS) and other demyelinating diseases is controversial, in part because widely used western blotting and ELISA methods either do not permit the detection of conformation-sensitive antibodies or do not distinguish them from conformation-independent antibodies. We developed a sensitive assay based on self-assembling radiolabeled tetramers that allows discrimination of antibodies against folded or denatured myelin oligodendrocyte glycoprotein (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
321
1
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 359 publications
(337 citation statements)
references
References 29 publications
9
321
1
6
Order By: Relevance
“…In the CSF, antigen microarrays in MS have detected antibodies to lipid (6) and ␣B-crystallin (23) and of note, the ␣B-crystallin reactive antibodies were of low affinity, detectable at 1:20 dilution (23). High-affinity autoreactive antibodies in the serum have not been consistently found in MS (24)(25)(26)(27)(28). We found that unique autoantibody signatures characterize RRMS, SPMS and PPMS based on reactivity to CNS antigens and HSP.…”
Section: Discussionmentioning
confidence: 77%
“…In the CSF, antigen microarrays in MS have detected antibodies to lipid (6) and ␣B-crystallin (23) and of note, the ␣B-crystallin reactive antibodies were of low affinity, detectable at 1:20 dilution (23). High-affinity autoreactive antibodies in the serum have not been consistently found in MS (24)(25)(26)(27)(28). We found that unique autoantibody signatures characterize RRMS, SPMS and PPMS based on reactivity to CNS antigens and HSP.…”
Section: Discussionmentioning
confidence: 77%
“…Increased frequencies of antibodies to MOG have been reported in the serum and CSF of MS patients relative to controls (Kennel De March et al, 2003), but other studies have found similar levels of anti-MOG in MS and other neurological diseases or controls (Brokstad et al, 1994;Lampasona et al, 2004;Mantegazza et al, 2004;Markovic et al, 2003;O'Connor et al, 2007;Reindl et al, 1999). Although detectable in some cases, the reported frequency of anti-MOG in serum and CSF from MS patients varies considerably between studies.…”
Section: Autoantibody Production By B Cellsmentioning
confidence: 99%
“…New methods have therefore been developed that enable specific detection of antibodies to properly folded and glycosylated MOG protein. The first method involves labeling of MOG transfectants with serum or CSF antibodies Lalive et al, 2006;O'Connor et al, 2007;Zhou et al, 2006), but the frequency of anti-MOG in MS still varies considerably between these studies, suggesting heterogeneity in the studied patient populations. The second method is a sensitive radioimmunoassay with a tetrameric version of folded and glycosylated MOG protein.…”
Section: Autoantibody Production By B Cellsmentioning
confidence: 99%
“…2 Also the recognition of specific and sensitive immune abnormalities in clearly defined clinical phenotypes (such as anti-Aquaporin-4 antibodies in neuromyelitis optica 3 ) suggests that discrete clinical and immunological diseases may exist within the spectrum of CNS inflammatory demyelination. Further examples of specific immune markers in discrete ADEM variants include the presence of antimyelin oligodendrocyte antibodies in a subgroup of ADEM, 4 and antibodies against basal ganglia components in post-streptococcal ADEM with dominant basal ganglia MRI lesions. 5 Further examination for these and other immune parameters may help 'split' the various ADEM variants, rather than 'lump' them all together, as occurs now.…”
mentioning
confidence: 99%
“…directed against cytokines, B-cells, T-cells, etc.). 3,4 Over the past decade, it has become increasingly clear that patients with multiple sclerosis have a spectrum of immune perturbations. It is likely that future therapies will become tailored and individualized according to the dominant pathogenic immune mechanism in each patient.…”
mentioning
confidence: 99%